2021
DOI: 10.1038/s41598-021-89617-2
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and metaregression of risk factors associated with mortality in hip fracture patients during the COVID-19 pandemic

Abstract: Incidence of hip fractures has remained unchanged during the pandemic with overlapping vulnerabilities observed in patients with hip fractures and those infected with COVID-19. We aimed to investigate the independent impact of COVID-19 infection on the mortality of these patients. Healthcare databases were systematically searched over 2-weeks from 1st–14th November 2020 to identify eligible studies assessing the impact of COVID-19 on hip fracture patients. Meta-analysis of proportion was performed to obtain po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…diabetes, dementia) were associated with higher mortality rates[ 45 ]. Extracapsular fractures are also an indicator of high mortality[ 46 ]. Smoking, alcohol consumption, and attitudes to COVID-19 may explain the higher prevalence in men than women[ 47 ].…”
Section: Management To Address the Issuementioning
confidence: 99%
“…diabetes, dementia) were associated with higher mortality rates[ 45 ]. Extracapsular fractures are also an indicator of high mortality[ 46 ]. Smoking, alcohol consumption, and attitudes to COVID-19 may explain the higher prevalence in men than women[ 47 ].…”
Section: Management To Address the Issuementioning
confidence: 99%
“…Reportedly, the mortality rate in COVID-19 negative hip fractures patients varied from 7.1–53.6%. 21 26 27 In addition, comparative studies of mortality rates of hip fracture with COVID-19 negative before and after the COVID-19 pandemic reported no significant increase in the mortality rate. 8 13…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patients regardless of COVID-19 status have yielded conflicting results when comparing the mortality of hip fracture patients treated during the COVID-19 pandemic to historical controls. Increased mortality was found in a cohort of 43 hip fracture patients in the United Kingdom compared to the same time period during the three years prior [ 41 ], and a meta-analysis of 2651 patients found an excess mortality of ~10% during the pandemic [ 21 ]. Another study in Spain, however, did not find a difference in 30-day mortality, similar to our study [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies across geographies have suggested that hip fracture patients who tested positive for COVID-19 had increased mortality [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Furthermore, meta-analyses have found a four- to seven-fold increase in mortality among patients with COVID-19 infection in comparison with those treated during the COVID-19 pandemic who did not have COVID-19 [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%